Programming mobile context-aware applications with TOTAM - Gonzalez Boix, Elisa; Scholliers, Christophe; De Meuter, Wolfgang; D’Hondt, Theo (The Journal of systems and software, 2014)
•We propose a novel tuple space model to support the development of context-aware applications deployed on mobile networks.•We discuss how current tuple space approaches can lead to erroneous perception of context.•We extend the notion of a tuple with a context rule that determines whether the tuple is in the right context or not.•We describe informally and formally our approach and demonstrate its applicability by means of various mobile applications.•Benchmarks show that our approach can lead to a significant increase in performance compared to other approaches. In tuple space approaches to context-aware mobile systems, the notion of context is defined by the presence or absence of certain tuples in the tuple space. Existing approaches define such presence either by collocation of devices holding the tuples or by replication of tuples across all devices. We show that both approaches can lead to an erroneous perception of context. Collocation ties the perception of context to network connectivity which does not always yield the expected result. Tuple replication can cause that a certain context is perceived even if the device has left the context a long time ago. We propose a tuple space approach in which tuples themselves carry a predicate that determines whether they are in the right context or not. We present a practical API for our approach and show its use by means of the implementation of various mobile applications. Benchmarks show that our approach can lead to a significant increase in performance compared to other approaches.